Seasonal variation and volatility of ultra-fine particles in coastal Antarctic troposphere - Keiichiro Hara; Kazuo Osada; Chiharu Nishita-Hara; Masanori Yabuki; Masahiko Hayashi; Takashi Yamanouchi; Makoto Wada; Masataka Shiobara (National Institute of Polar Research, 2010)
The Size distribution and volatility of ultrafine aerosol particles were measured at Syowa Station during the 46-47 Japanese Antarctic Research Expeditions. During the summer, most of the ultrafine particles were volatile particles, which were composed of H_2SO_4, CH_3SO_3H and sulfates bi-sulfates. The abundance of non-volatile particles was ～ 20% during the summer, increasing to>90% in winter-spring. Non-volatile particles in winter were dominantly sea-salt particles. Some ultrafine sea-salt particles might be released from sea-ice. When air mass was transported from the free troposphere over the Antarctic continent, the abundance of non-volatile particles dropped to<30% even in winter.